(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This research focused on the Assessment of E-waste Management on Records Management of Messy Bessy Cleaners Inc. Records are essentially valuable to a company's operation, as well as organizing and keeping records is essential for the business to sustain its operation (Premakaruma, 2016). E-waste issues and measures become a challenge to entities. The researchers conducted an assessment of e-waste management to assess the company's e-waste issues and measures and the effect on records management to provide awareness and possible improvements (Lansang, 2019). Messy Bessy was chosen to be studied as they have a need to improve e-waste management in their records management. This study revealed that the problems encountered by the respondents give rise to having a records officer who will focus on records and E-waste management, wherein the records officer is recommended to Plan, Create, Implement, and Evaluate standard guidelines to be used in records and E-waste Issues and measures. In accordance with the findings of the study, the research shows that Messy Bessy employees encounter problems in assessing e-waste due to a lack of knowledge to process e-waste management. The result of the research revealed that Messy Bessy has a need to address the problems encountered in E-waste Management to provide solutions. The Demographic Profile of the respondents does not affect the process of assessing E-waste Management.